The Role of Stakeholders in the Development of Gapoktan Sidomakmur - Hendriawan, Jemi; Suminah, Suminah; Suwarto, Suwarto (SERUNAI, 2023)
The role of stakeholders affect the implemented programme such as member participation and the impact of the role. This research used qualitative approach with descriptive method. The research method applied in this descriptive approach was a case study. The determination of informants was carried out by purposive sampling with key informants and snowball sampling techniques, a total of 12 informants. Data validity used triangulation as a method to validate the data. The results showed that the development of Gapoktan Sidomakmur in the food security programme involved five main roles of stakeholders. These roles included policy-making by the Bojonegoro District DKPP and Purwosari Village Government as policy makers, coordination by the Gapoktan chairperson and farmer groups as coordinators, and facilitator roles by BPP, PPLs, Village Facilitators, and Purwosari Village Government. Programme implementation involved members of Gapoktan, farmer groups, and the Purwosari Village Government as implementers, as well as the role of accelerators by the Purwosari District Government, PPLs, and Village Facilitators. Although cooperation between stakeholders in the development of Gapoktan Sidomakmur in Purwosari Village is quite good, not all stakeholders are fully involved in carrying out their roles, which was evident from the lack of maximum support for Gapoktan Sidomakmur’s programmes.